Profesional ethics in the legal profesion. An examination on the conduct and etiquette of lawyers with reference to the legal profession (practice and etiquette) Rules 1978 / Abd. Aziz Halim Al-Azhari - Al-Azhari, Abd. Aziz Halim (Faculty of Law, 1984)
As a result of today's modern society's complexity. it is highly demanded that the legal profession playa major role in giving practical guidance to the public. This would include giving advice relating to life. property and other rights which extend beyond the strict interpretation of law. The complexity of the various transactions and services rendered by the lawyers to the public would make the role of lawyers in serving the community greatly felt particularly in a developing country like Malaysia today. Due to that, a close interaction exists between lawyers and the general public. As lawyers exist to serve the public.he is the great saver of justice as "Justice is the great interest of man on earth" Lawyers should be trained to pursue the law in a high spirit of public services. LAW 1987